Does Integration Policy Integrate? The Employment Effects of Sweden's 2010 Reform of the Introduction Program - Haodong Qi; Nahikari Irastorza; Henrik Emilsson; Pieter Bevelander (Institute of Labor Economics (IZA), 2019)
Sweden, like many other European countries, has seen a surge in refugee immigrants over recent years, which raises a concern about the labour market integration of these newcomers. This paper investigates whether integration policy may improve refugees' labour market performance. Specifically, we examine the employment effects of the 2010 reform of the introduction program (known as IP), and how the effects vary depending on refugees' educational attainment. Given that the eligibility for the new IP was exogenously determined by whether the refugee status was granted before or after December 1, 2010, we identify the employment effects by comparing those who participated in the new IP (treatment group), with those who participated in the old IP (control group). Using a triple difference method, we find positive employment effects of the new IP that exacerbate over time. The effects are significant and identical for male refugees, regardless of educational attainment; in contrast, the effects of program participation for refugee women vary by education level, and are greater for high-educated women than that for the low-educated counterparts.
Keywords: J62; J68; 330; labour market policy; employment; refugees